Déficit de atención hiperactividad y su incidencia en el rendimiento escolar de los niños de 7 años - López Ramírez, María Fernanda (2015)
This investigation carried out in the mixed particular school His Corner of Light in which it was observed that the teachers were not applying methodological strategies adapted for the good performance of the children who have hyperactivity with attention deficit. The children who present disorder of deficit of attention with hyperactivity, are children who by its attitude are not accepted in the society really for this reason we focus in significant learning that is in which it prevails the social adaptations from this point we set off to develop diverse strategies to adapt the child to the group of its partners facilitating the daily coexistence to him with the environment that surrounds it referring to its family, teachers and partners, it is necessary to stress that while earlier it is the intervention of the child who presents this disorder, better the results will be that we will obtain all this it goes to depend on the strategies that will be used during the treatment…..